Bone defect reconstruction with autologous bone inactivated with liquid nitrogen after resection of primary limb malignant tumors: An observational study - Li, Yuan (Medicine (Baltimore), 2020)
Surgical treatment of malignant bone tumors comprises tumor resection and reconstruction. The most commonly used reconstruction method is prosthesis replacement, which achieves good early function, but has a high long-term incidence of complications. Another reconstruction option is autologous bone replantation, which has the advantages of anatomical matching and no need for large bone bank support. Few studies have evaluated reconstruction with liquid nitrogen-inactivated autogenous bone. The present study aimed to evaluate the oncological results, bone healing results, complications, and indications of reconstruction with liquid nitrogen-inactivated autogenous bone grafts. The study population comprised 21 consecutive patients. The tumor site was the tibia in 9 cases, femur in 8, and humerus in 4. There were 37 osteotomy ends in total. After freezing and rewarming, the medullary cavity of the autogenous bone was filled with antibiotic bone cement. Seventeen patients received bilateral plate fixation, 2 received intramedullary nail and distal plate fixation, and 2 received single plate fixation. The average follow-up was 31 ± 6 months. Eighteen patients survived without tumors, and the 3-year survival rate was 80.4%. All cases had adequate surgical margins, but recurrence developed in 1 patient. Metastasis occurred in 3 patients, who all died of metastasis. Intraoperative inactivated bone fracture occurred in 1 patient, and screw breakage was found in 1 patient. Nonunion occurred at 1 humeral diaphysis osteotomy site, and 1 patient was lost to follow-up; the average healing time of the other 35 ends was 13 ± 6 months, and the bone healing rate was 97.2%. The average bone healing times in the metaphysis and diaphysis were 9 ± 3 months and 15 ± 6 months (P = .003). The average bone healing times in the upper and lower limbs were 16.6 ± 7.4 months and 12.3 ± 5.8 months (P = .020). The average Muscle and Skeletal Tumor Society score was 28 ± 3 (21–30) in the 18 survivors. Liquid nitrogen-inactivated autologous bone replantation for primary malignant limb tumor was safe and effective, as shown by the relatively low complication rate, high bone healing rate, and satisfactory postoperative function. This is a reliable biological reconstruction method for malignant bone tumors with specific site and bone destruction characteristics.